2018
DOI: 10.1186/s12872-018-0966-2
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac autotransplantation and ex vivo surgical repair of giant left atrium: a case presentation

Abstract: BackgroundChronic Mitral Valve disease is strongly associated with Left atrial enlargement; the condition has a high mortality risk. Clinical manifestations include atrial fibrillation, pulmonary hypertension, thromboembolic events, and in cases of Giant Left Atrium (GLA) and a distorted cardiac silhouette. Full sternotomy, conventional open-heart surgery, reductive atrioplasty and atrioventricular valve repair are required to resolve symptoms. However, these procedures can be complicated due to the posterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Exploiting the improved access routes to critically located tumors, various case studies in cardiac surgery have reported successful ex vivo resections of cardiac sarcoma ( 200 ), complex atrial myofibroblastic tumors ( 201 ), and giant large atria following chronic mitral valve disease on an ex vivo beating heart ( 202 ). Moreover, single centers also have reported on larger case numbers of cardiac autotransplantation with ex vivo tumor resection for malignant complex primary left heart tumors ( 203 ) ( Figure 2G ).…”
Section: Potential Of Evmp Beyond Ordinary Graft Preservationmentioning
confidence: 99%
“…Exploiting the improved access routes to critically located tumors, various case studies in cardiac surgery have reported successful ex vivo resections of cardiac sarcoma ( 200 ), complex atrial myofibroblastic tumors ( 201 ), and giant large atria following chronic mitral valve disease on an ex vivo beating heart ( 202 ). Moreover, single centers also have reported on larger case numbers of cardiac autotransplantation with ex vivo tumor resection for malignant complex primary left heart tumors ( 203 ) ( Figure 2G ).…”
Section: Potential Of Evmp Beyond Ordinary Graft Preservationmentioning
confidence: 99%